Influence Sustainable Hospitality Policy on Interest Visitor in Choosing an Eco- Friendly Hotel - Putri, Fitri Ayu Triana (Politeknik Siber Cerdika Internasional, 2024)
Increasing awareness will issue global sustainability has push industry hospitality For adopt sustainable hospitality policies , which focus on sustainable practices friendly environment like subtraction waste , savings energy , and use source Power renewable . However , it is still A little research that is special to study influence policy This to interest visitor in choose a friendly hotel environment , especially in Indonesia. Research This aiming For analyze to what extent do sustainable hospitality policies influence interest visitor in choose accommodation that implements practice sustainability . Research use approach quantitative with method survey of 200 respondents who have experience stay at a friendly hotel environment in Indonesia. Data collection was carried out through questionnaire closed with Likert scale , which is then analyzed use simple linear regression For see influence variable policy sustainability to interest guest . Research results show that sustainable hospitality policy has influence significant to interest visitor in choose a friendly hotel environment , with Respondent more tend choose a hotel that implements practice sustainability . Research This show that implementation policy friendly environment No only support global sustainability but also enhance Power attraction and loyalty Consumers . Findings This expected can become reference for industry hospitality in designing effective sustainability strategies .?